Orthostatic hypotension: a pragmatic guide to diagnosis and treatment. Issue 11 (30th October 2020) - Gibbon, Jake Ryan; Frith, James
Abstract: Topics for DTB review articles are selected by DTB's editorial board to provide concise overviews of medicines and other treatments to help patients get the best care. Articles include a summary of key points and a brief overview for patients. Articles may also have a series of multiple choice CME questions.